Strengthening Mountain Societies in Central Asia in a Context of Multidimensional Change - Schmidt-Vogt, Dietrich; Foggin, Marc; Hergarten, Christian (Mountain research and development, 2016)
The Mountain Societies Research Institute (MSRI) conducts transdisciplinary research for development, with the goal of improving the livelihoods and well-being of mountain societies in Central Asia and building their resilience in a rapidly changing socioeconomic, political, and biophysical environment. MSRI is a core institute of the Graduate School of Development at the University of Central Asia (UCA), working alongside the Institute of Public Policy and Administration (IPPA). Beyond research, MSRI also engages in building Central Asian capacities to contribute to sustainable mountain development; serves as a knowledge hub for scholars, development practitioners, and policy-makers; and contributes to the development of UCA's academic programs, which will be offered in the Kyrgyz Republic, Tajikistan, and Kazakhstan. The University is now ready to inaugurate its undergraduate program, with students coming from across Central Asia to its Naryn Campus in the Kyrgyz Republic in September 2016. MSRI is currently headquartered in Bishkek, Kyrgyz Republic, but, in the longer term, will be affiliated most closely with the Khorog Campus in Tajikistan, which is set to open in September 2017. MSRI will collaborate closely with UCA's Earth and Environmental Sciences Program, with contributions to teaching supported by innovative, applied research embedded in the University's Learning Landscapes initiative. MSRI's development vision and research strategy are focused on addressing the multidimensional nature of current and anticipated changes in mountain areas of Central Asia and on building resilience in mountain societies.